The impact of enhancing self-management support for diabetes in Community Health Centers through patient engagement and relationship building: a primary care pragmatic cluster-randomized trial. Issue 9 (7th October 2022) - Hessler, Danielle; Fisher, Lawrence; Dickinson, Miriam; Dickinson, Perry; Parra, José; Potter, Michael B
Abstract: Type 2 diabetes (T2DM) self-management support (SMS) programs can yield improved clinical outcomes but may be limited in application or impact without considering individuals' unique social and personal challenges that may impede successful diabetes outcomes. The current study compares an evidence-based SMS program with an enhanced version that adds a patient engagement protocol, to elicit and address unique patient-level challenges to support improved SMS and diabetes outcomes. Staff from 12 Community Health Center (CHC) clinical sites were trained on and delivered: Connection to Health (CTH; 6 sites), including a health survey and collaborative action planning, or Enhanced Engagement CTH (EE-CTH; 6 sites), including additional relationship building training/support. Impact of CTH and EE-CTH on behavioral self-management, psychological outcomes, and modifiable social risks was examined using general linear mixed effects. Clinics enrolled 734 individuals with T2DM (CTH = 408; EE-CTH = 326). At 6- to 12-month postenrollment, individuals in both programs reported significant improvements in self-management behaviors (sugary beverages, missed medications), psychological outcomes (stress, health-related distress), and social risks (food security, utilities; all p < .05). Compared with CTH, individuals in EE-CTH reported greater decreases in high fat foods, salt, stress and health-related distress; and depression symptoms improved within EE-CTH (all p < .05). CTH and EE-CTH demonstrated positive behavioral, psychological, and social risk impacts for T2DM in CHCs delivered within existing clinical work flows and a range of clinical roles. Given the greater improvements in psychological outcomes and behavioral self-management in EE-CTH, increased attention to relationship building strategies within SMS programs is warranted. Abstract : Individuals with type 2 diabetes receiving care at Community Health Centers reported decreases in stress and social risks and increases in self-management behaviors after participating in either of two self-management support programs.